Pengembangan Media Evaluasi Berbasis Digital Blooket Materi Fase Perkembangan Islam di Nusantara untuk Meningkatkan Minat Belajar Siswa - Aulia, Nor Heni; Jasiah, Jasiah (YASIN, 2025)
This study is motivated by the low student interest in the Islamic Cultural History (SKI) subject at MA Darul Ulum Palangka Raya, which is attributed to the use of conventional evaluation methods and the limited application of interactive digital media. The aim of this research is to develop and assess the feasibility of a digital evaluation medium using Blooket as an interactive alternative for SKI learning. The method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate). The research subjects included media experts, content experts, and 20 students from class XII C. Instruments consisted of validation sheets and student response questionnaires. Validation results showed that Blooket received a score of 95% from media experts and 90% from content experts, categorized as "Highly Valid" and "Feasible." Field trials indicated a significant increase in student learning interest, with an average score of 4.68 in the "Very High" category. These findings demonstrate that Blooket is effective as an interactive and enjoyable evaluation tool that enhances student participation in SKI learning. The implications of this study support the adoption of game-based digital evaluation media as an innovative alternative in Islamic Religious Education, particularly in SKI, to boost student motivation and engagement in the digital era.